Tingkat Keramahan Alat Tangkap Bouke Ami yang di Daratkan di Pelabuhan Perikanan Nusantara Muara Angke - Ika Anjani; Achmad Kusyairi; Exist Saraswati (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
The utilization of Bouke Ami fishing gear in Indonesian waters, particularly in PPN Muara Angke, plays a significant role in managing fishery resources and increasing production. This gear is commonly used by fishermen to catch pelagic fish such as mackerel, tuna, and squid. However, the environmental friendliness of Bouke Ami fishing gear is crucial for sustainable fisheries management. While effective in catching fish, this fishing gear can negatively impact the marine ecosystem, including damage to coral reefs and the capture of juvenile fish, which affects their growth. This research aims to assess the level of environmental friendliness of the Bouke Ami fishing gear used in PPN Muara Angke. Conducted from November 2025 to January 2026, the study employed a descriptive method, using interviews and questionnaires with Bouke Ami fishermen. The findings are expected to contribute to the literature on sustainable fisheries and highlight the importance of using environmentally friendly fishing gear, in line with the Code of Conduct for Responsible Fisheries.